2019
DOI: 10.1007/s00216-019-01607-6
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNAs: from genomic junk to rising stars in the early detection of cancer

Abstract: Despite having been underappreciated in favor of their protein-coding counterparts for a long time, long noncoding RNAs (lncRNAs) have emerged as functional molecules, which defy the central dogma of molecular biology, with clear implications in cancer. Altered expression levels of some of these large transcripts in human body fluids have been related to different cancer conditions that turns them into potential non-invasive cancer biomarkers. In this review, a brief discussion about the importance and current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 42 publications
(41 reference statements)
0
27
0
Order By: Relevance
“…Unlike ctDNA the mRNA copy number is larger than two, up to thousands copies, so their concentration in fluids is higher (Siravegna et al, 2017). Non-coding RNAs, formerly known as dark matter, are now regarded as crucial molecules in cancer biology (Miranda-Castro et al, 2019). The shorter RNAs (mi-RNA) have been studied more intensively than the longer counterparts (lncRNA) but both are promising markers in spite of the presence of ribonucleases because they used to be encapsulated in EV or linked to other macromolecules (Wang et al, 2019a).…”
Section: Targets In Liquid Biopsiesmentioning
confidence: 99%
“…Unlike ctDNA the mRNA copy number is larger than two, up to thousands copies, so their concentration in fluids is higher (Siravegna et al, 2017). Non-coding RNAs, formerly known as dark matter, are now regarded as crucial molecules in cancer biology (Miranda-Castro et al, 2019). The shorter RNAs (mi-RNA) have been studied more intensively than the longer counterparts (lncRNA) but both are promising markers in spite of the presence of ribonucleases because they used to be encapsulated in EV or linked to other macromolecules (Wang et al, 2019a).…”
Section: Targets In Liquid Biopsiesmentioning
confidence: 99%
“…They may function as oncogenes or tumour suppressors [34]. Apart from their low concentration (~femtomolar level) in body fluids of early-stage cancer patients, the strong intramolecular secondary structure of ncRNAs due to their large size is also a challenge for the determination of lncRNAs [35].…”
Section: Long Non-coding Rnasmentioning
confidence: 99%
“…To date, multiple lncRNAs have been identified in CRC [ 29 ] and several studies have shown their involvement in key biological processes, from transcriptional regulation [ 30 , 31 , 32 , 33 ], to cellular mechanisms [ 34 , 35 , 36 , 37 , 38 ], and tumor progression [ 39 ]. Some reports have shown that cancer cells secrete lncRNAs into biological fluids [ 40 , 41 ]. This mechanism suggests that oncogenic signals can be spread to other cells, and it opens interesting perspectives for biomarker discovery [ 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%